Stem Cell Breakthroughs: A Cure in Sight? - Mittal, Avi; Malik, Nikita; Sihmar, Kavita; Soni, Nazuk; Priyanka; Kumar, Hemant; Ajay; Sujal (Medical Science: Trends and Innovations Vol. 4, 2025)
Stem cells, characterized by their remarkable abilities for self-renewal and differentiation, are at the forefront of regenerative medicine, offering transformative potential for treating a spectrum of degenerative diseases. The journey of stem cell therapy began in 1958 and has evolved significantly, with pivotal advancements such as the isolation of embryonic stem cells in 1998 and the creation of induced pluripotent stem cells [iPSCs] in 2006. Different stem cell types—ranging from hematopoietic to mesenchymal and neural stem cells—show promise in addressing conditions like neurological disorders, autoimmune diseases, and haematological disorders. Despite their therapeutic potential, ethical dilemmas remain a significant challenge, particularly concerning embryonic stem cells, which prompt ongoing debates about the moral implications of their use. As the field progresses, addressing safety, efficacy, and equitable access to stem cell therapies is critical. Innovative delivery systems and methodologies are being developed to enhance the effectiveness of these therapies while minimizing associated risks. Looking ahead, research will focus on harnessing the full potential of stem cells, elucidating the molecular pathways that govern their differentiation, and navigating the ethical landscape. Through these efforts, we may pave the way for ground-breaking treatments that could redefine the future of healthcare and improve patient outcomes across various conditions.